2015
DOI: 10.3389/fnins.2015.00068
|View full text |Cite
|
Sign up to set email alerts
|

Auditory distraction transmitted by a cochlear implant alters allocation of attentional resources

Abstract: Cochlear implants (CIs) are auditory prostheses which restore hearing via electrical stimulation of the auditory nerve. The successful adaptation of auditory cognition to the CI input depends to a substantial degree on individual factors. We pursued an electrophysiological approach toward an analysis of cortical responses that reflect perceptual processing stages and higher-level responses to CI input. Performance and event-related potentials on two cross-modal discrimination-following-distraction (DFD) tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 63 publications
6
29
1
Order By: Relevance
“…This conclusion is confirmed by the positive correlation between the N2/N4 latency and the ratings of the listening effort. In summary, the N2/N4 results support the view that the limited quality of the CI input leads to prolonged neural processing of speech, more effortful listening, and higher susceptibility to noisy background conditions (Finke et al, 2015;Hochmair-Desoyer et al, 1997;Rönnberg et al, 2013;Zeng et al, 2011).…”
Section: Lexical and Semantic Speech Processingsupporting
confidence: 58%
See 2 more Smart Citations
“…This conclusion is confirmed by the positive correlation between the N2/N4 latency and the ratings of the listening effort. In summary, the N2/N4 results support the view that the limited quality of the CI input leads to prolonged neural processing of speech, more effortful listening, and higher susceptibility to noisy background conditions (Finke et al, 2015;Hochmair-Desoyer et al, 1997;Rönnberg et al, 2013;Zeng et al, 2011).…”
Section: Lexical and Semantic Speech Processingsupporting
confidence: 58%
“…It is likely that the slow-down of the N2/N4 latency is related to the limited CI input which only partially matches to the attributes stored in the long-term memory (lexical representation), requiring additional explicit processing of the (limited) information transmitted by the CI (Finke et al, 2015;Rönnberg et al, 2013). One may speculate that in noisy background conditions the N2/N4 latency is further prolonged, given that the mismatch between the CI input and the cortical representation would be enhanced in difficult listening conditions.…”
Section: Lexical and Semantic Speech Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the CI outcome is related to higher-order resources such as verbal abilities or working memory (WM) capacity [Finke et al, 2015[Finke et al, , 2016Kral et al, 2016;Rönnberg et al, 2013]. According to the Ease of Language Understanding model by Rönn-berg et al [2013], WM capacity is needed to support speech understanding via an explicit processing loop in adverse listening conditions, such as listening via a CI.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies, the neuronal processes underlying speech perception were examined in CI users with an oddball paradigm [Beynon et al, 2005;Finke et al, 2015Finke et al, , 2016Groenen et al, 2009;Henkin et al, 2009]. In a series of standard syllables or words, infrequent deviant stimuli were intermixed, and participants were asked to respond to these infrequent targets [Polich, 2007].…”
Section: Introductionmentioning
confidence: 99%